Impact of remdesivir according to the pre-admission symptom duration in patients with COVID-19. (2nd September 2021) - Garcia-Vidal, Carolina; Alonso, Rodrigo; Camon, Ana M; Cardozo, Celia; Albiach, Laia; Agüero, Daiana; Marcos, M Angeles; Ambrosioni, Juan; Bodro, Marta; Chumbita, Mariana; de la Mora, Lorena; Garcia-Pouton, Nicole; et al.
Abstract: Background: The use of remdesivir has demonstrated a significant reduction in the time to recovery in patients with COVID-19. However, the impact on mortality is still controversial. Therefore, it is necessary to evaluate whether there is a specific subgroup of patients in whom an active antiviral therapy also reduces the mortality. Methods: Patients admitted for >48 h in our hospital for a SARS-CoV-2 confirmed or suspected infection from February 2020 to February 2021 were retrospectively analysed. The primary outcome of the study was mortality at 30 days. Univariate and multivariate analyses were performed to identify predictors of mortality. Results: In total, 2607 patients (438 receiving remdesivir and 2169 not) were included with a median (IQR) age of 65 (54–77) years and 58% were male. Four hundred and seventy-six were admitted to the ICU (18.3%) and 264 required invasive mechanical ventilation (10.1%). The global 30 day mortality rate was 10.7%. Pre-admission symptom duration of 4–6 days and ≤3 days was associated with a 1.5- and 2.5-fold increase in the mortality rate, respectively, in comparison with >6 days and treatment with remdesivir was independently associated with a lower mortality rate (OR = 0.382, 95% CI = 0.218–0.671). The analysis showed that the major difference was among patients with shorter pre-admission symptom duration (<6 days). Conclusions: Patients with ≤3 days and 4–6 days from symptom onset to admission are associated with a 2.5- and 1.5-fold higher risk of death, respectively. Remdesivir was associated with 62% reduced odds of death versus standard-of-care and its survival benefit increased with shorter duration of symptoms.